Analisis Pengelolaan Sampah di Pondok Pesantren Ibnul Qoyyim Putri Sebagai Implementasi Tujuan Pembangunan Berkelanjutan - Laily Novika Nurdiani; Azis Muslim (Jurnal Pengendalian Pencemaran Lingkungan (JPPL), 2022)
Sustainable development is a global agenda which is better known as the Sustainable Development Goals (SDGs) and scheduled to start in 2016-2030, from the 17 SDGs goals, there are 3 goals that promote waste reduction and climate change mitigation, namely the 6th goal on clean water and proper sanitation, the 13th goal of dealing with climate change and the 14th goal of protecting marine ecosystems. Analysis of Waste Management at the Ibnul Qoyyim Putri Islamic Boarding School that located in Yogyakarta is an attempt to show that waste management in the school institutional is able to have an impact on individuals and has relevance to the three SDGs goals above. This study uses a qualitative descriptive method with a sociological approach where researchers allow natural interviews to obtain objective research results. Based on the results of the study, waste management in PP Ibnul Qoyyim was able to raise awareness of the majority of students and teachers about the importance of managing waste as evidenced by the reduction in waste that accumulates in landfills, a cleaner and more organized environment to the growing awareness that by processing waste one can protect nature for sustainability. For future generations, this waste management is also relevant to the SDGs goals 6, 13 and 14 and is able to increase the creativity of students in utilizing recycled waste.